The portrait of Dorian Gray: spontaneous expression of happiness is an invariant kinematic marker - Straulino, Elisa; Scarpazza, Cristina; Miolla, Alessio; Spoto, Andrea; Betti, Sonia; Sartori, Luisa (Frontiers in Psychology, 2025)
Crucial changes in the dynamical development of a facial display can characterize and distinguish spontaneous and posed facial expressions, a topic that has been poorly investigated. To assess spontaneous expressions of happiness, we presented video clips extracted from comedies showing hilarious scenes (Emotional Induction, Experiment 1) or videoclips showing smiling faces (Motor Contagion, Experiment 2). To induce posed expressions, we adopted the classic image of posed happiness from Ekman’s dataset. The results showed high consistency for spontaneous expressions of happiness, characterized by reduced amplitude, speed and deceleration peaks of the smile and lower eyebrow distance compared to posed expressions, for both methods of emotion induction. Overall, we demonstrated that high-definition 3-D kinematics of dynamic facial movements together with FACS coding can provide relevant details to characterize the syntax of dynamic facial displays, showing that spontaneous expression of happiness is an individual fingerprint, unaltered by mood induction procedures. However, spontaneous smiling varied at the individual level, influenced by participants’ predisposition to cognitively empathize with the movie protagonist. These findings are significant for emotion research, which has largely overlooked the impact of mood induction methods and their relationship with interindividual variability.